Physical activity of electric bicycle users compared to conventional bicycle users and non-cyclists: Insights based on health and transport data from an online survey in seven European cities. (June 2019) - Castro, Alberto; Gaupp-Berghausen, Mailin; Dons, Evi; Standaert, Arnout; Laeremans, Michelle; Clark, Anna; Anaya-Boig, Esther; Cole-Hunter, Tom; Avila-Palencia, Ione; Rojas-Rueda, David; Nieuwenhuijsen, Mark; Gerike, Regine; et al.
Abstract: Physical activity has been widely associated with beneficial health effects. The use of electric-assist bicycles (e-bikes) can lead to increased or decreased physical activity, depending on the transport mode substituted. This study aimed to compare physical activity levels of e-bikers and conventional bicycle users (cyclists) as well as across e-bike user groups based on the transport mode substituted by e-bike. Physical activity, transport and user related parameters were analysed. Data from the longitudinal on-line survey of the PASTA project were used. The survey recruited over 10, 000 participants in seven European cities. Physical activity levels, measured in Metabolic Equivalent Task minutes per week (MET min/wk), were similar among e-bikers and cyclists (4463 vs. 4085). E-bikers reported significantly longer trip distances for both e-bike (9.4 km) and bicycle trips (8.4 km) compared to cyclists for bicycle trips (4.8 km), as well as longer daily travel distances for e-bike than cyclists for bicycle (8.0 vs. 5.3 km per person, per day, respectively). Travel-related activities of e-bikers who switched from cycling decreased by around 200 MET min/wk., while those switching from private motorized vehicle and public transport gained around 550 and 800 MET min/wk. respectively. Therefore, this data suggests that e-bike use leads to substantial increases in physical activity in e-bikers switching from private motorized vehicle and public transport, while net losses in physical activity in e-bikers switching from cycling were much less due to increases in overall travel distance. Highlights: E-bikers take longer trips by e-bike and bicycle, compared to cyclists. Physical activity gains from active travel are similar in e-bikers and cyclists. Substituting all car trips with e-bike use leads to a gain of 550 MET min/week. Transport mode substituted by the e-bike is still used frequently afterwards.